Correlative and dynamic imaging of the hatching biology of Schistosoma japonicum from eggs prepared by high pressure freezing. - Malcolm K Jones; Sze How Bong; Kathryn M Green; Philadelphia Holmes; Mary Duke; Alex Loukas; Donald P McManus (PLoS Neglected Tropical Diseases, 2008)
BACKGROUND: Schistosome eggs must traverse tissues of the intestine or bladder to escape the human host and further the life cycle. Escape from host tissues is facilitated by secretion of immuno-reactive molecules by eggs and the formation of an intense strong granulomatous response by the host which acts to exclude the egg into gut or bladder lumens. Schistosome eggs hatch on contact with freshwater, but the mechanisms of activation and hatching are poorly understood. In view of the lack of knowledge of the behaviour of egg hatching in schistosomes, we undertook a detailed dynamic and correlative study of the hatching biology of Schistosoma japonicum. METHODOLOGY/PRINCIPAL FINDINGS: Hatching eggs of S. japonicum were studied using correlative light and electron microscopy (EM). The hatching behaviour was recorded by video microscopy. EM preparative methods incorporating high pressure freezing and cryo-substitution were used to investigate ultrastructural features of the miracidium and extra-embryonic envelopes in pre-activated and activated eggs, and immediately after eggshell rupture. Lectin cytochemistry was performed on egg tissues to investigate subcellular location of specific carbohydrate groups. CONCLUSIONS/SIGNIFICANCE: The hatching of S. japonicum eggs is a striking phenomenon, whereby the larva is liberated explosively while still encapsulated within its sub-shell envelopes. The major alterations that occur in the egg during activation are scission of the outer envelope-eggshell boundary, autolysis of the cellular inner envelope, and likely hydration of abundant complex and simple polysaccharides in the lacunal space between the miracidial larva and surrounding envelopes. These observations on hatching provide insight into the dynamic activity of the eggs and the biology of schistosomes within the host.